Noble approach to control vibration using minimum quantity lubrication (MQL) in micro milling - Yeakub Ali, Mohammad; Ali Khan, Ahsan; Abd Rahman, Mohamed; Mohamed Ariff, Tasnim Firdaus (2019)
The increasing demands for miniaturized products especially in biomedical, electronics, and aerospace have obliged the manufacturers to fabricate complex micro parts with high accuracy and nano surface finish. Tool based micro milling is a flexible process to produce three dimensional miniaturized parts. But, micro milling leads to high interactions and friction between tool and workpiece resulting in high temperature and vibration which impair accuracy and surface quality. In conventional approach, cutting fluids are used to cool, lubricate and to remove the generated heat from the machining zone. However, huge amount of cutting fluid leads to environmental contamination. Thus, recently minimum quantity lubrication (MQL) method is introduced to remove the generated heat from the machining zone. This MQL is more environmental friendly and considered aligned with green manufacturing. However, the application of MQL does not eliminate the vibration issue which impair the stability of the micro milling operation. In addition, the level of instability in the presence of MQL is not fully discovered. Thus, a comprehensive model was established to represent the relationship between the vibration and micro milling parameters in the presence of MQL to estimate machining accuracy and surface quality. In this research the vibration characteristics of micro milling was investigated. The mathematical model among the vibration characteristics and micro milling parameters in presence of MQL was formulated. The root cause of vibration was measured by using an accelerometer and was analyzed using a specturm analyzer software. Experimental data using statistical software was analyzed for empirical model. The developed process is more environmental friendly in producing micro products with high precision and nano surface finish. This contributed to the body of knowledge in micromachining and eventually impact positively on national and international economy.